The interaction between family law, succession law and private international law adapting to change - Scherpe, Jens M. 1971-; Bargelli, Elena ca. 20./21. Jh (European family law series, 2021)
There can be no doubt that both substantive family and succession law engage in significant interaction with private international law, and, in particular, the European Union instruments in the field. While it is to be expected that substantive law heavily influences private international law instruments, it is increasingly evident that this influence can also be exerted in the reverse direction. Given that the European Union has no legislative competence in the fields of family and succession law beyond cross-border issues, this influence is indirect and, as a consequence of this indirect nature, difficult to trace. This book brings together a range of views on the reciprocal influences of substantive and private international law in the fields of family and succession law. It outlines some key elements of this interplay in selected jurisdictions and provides a basis for discussion and future work on the reciprocal influences of domestic and European law.